A Fuzzy Collaborative Sensor Network for Semiconductor Manufacturing Cycle Time Forecasting - Yu-Cheng Lin; Toly Chen; Yu-Cheng Wang (International Journal of Distributed Sensor Networks)
Network based sensing has become an important field of research, and it is expected that new applications of remote sensing will be developed. A fuzzy collaborative sensor network is developed in this study to predict the cycle time of a job in a semiconductor manufacturing factory, which is an important task for the factory. In the fuzzy collaborative sensor network, each sensor detects the status of a particular job as well as various environmental conditions present in the factory and uses a fuzzy neural network to analyze the received information. Each sensor communicates its settings and forecasting results to other sensors with the aid of a central control unit. According to the experimental results, the aggregate forecasting performance was considerably improved through the sensors' collaboration.